Diurnal and seasonal variation of the brain serotonin system in healthy male subjects - Matheson, Granville J.; Schain, Martin; Almeida, Rita; Lundberg, Johan; Cselényi, Zsolt; Borg, Jacqueline; Varrone, Andrea; Farde, Lars; Cervenka, Simon (NeuroImage (Orlando, Fla.), 2015)
The mammalian circadian clock underlies both diurnal and seasonal changes in physiology, and its function is thought to be disturbed in both seasonal and non-seasonal depression. In humans, molecular imaging studies have reported seasonal changes in the serotonin system. Despite the role of the circadian clock in generating seasonal physiological changes, however, diurnal variation of serotonin receptors and transporters has never been directly studied in humans. We used positron emission tomography to examine diurnal and seasonal changes in the serotonin 5-HT1A receptor and serotonin transporter in two large cohorts of healthy male subjects, employing a cross-sectional design. In 56 subjects measured with [11C]WAY-100635, we observed diurnal increases in the availability of 5-HT1A receptors in the cortex. In 40 subjects measured with [11C]MADAM, a decrease in 5-HTT was observed in the midbrain across the day. We also found seasonal changes in the 5-HT1A receptor in serotonin projection regions, with higher availability on days with a longer duration of daylight. Our observation that serotonin receptor and transporter levels may change across the day in humans is corroborated by experimental research in rodents. These findings have important implications for understanding the relationship between the circadian and serotonin systems in both the healthy brain and in affective disorders, as well as for the design of future molecular imaging studies. •We examined diurnal and seasonal changes in 5-HT1A and 5-HTT availability using PET.•An increase in 5-HT1A receptor availability was observed across the day in the cortex.•A decrease in 5-HTT availability was observed across the day in the midbrain.•Seasonal changes were found for 5-HT1A receptor availability in projection regions.•Findings may increase understanding of circadian and serotonin system interactions.